2000
DOI: 10.1007/s11661-000-0106-2
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of the microstructure and fracture toughness of the heat-affected zones of an SA 508 steel

Abstract: In this study, microstructures of a heat-affected zone (HAZ) of an SA 508 steel were identified by Mössbauer spectroscopy in conjunction with microscopic observations, and were correlated with fracture toughness. Specimens with the peak temperature raised to 1350 ЊC showed mostly martensite. With the peak temperature raised to 900 ЊC, the martensite fraction was reduced, while bainite or martensite islands were formed because of the slow cooling from the lower austenite region and the increase in the prior aus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 13 publications
2
19
0
Order By: Relevance
“…The strengths of the fusion zone and each sub-zone within the HAZ were increased mainly by the generation of martensite. Some researchers [39,40] have investigated the correlation between the microstructure and the fracture toughness within the heat affected zone in SA508 steel. Lee et al [40] reported that the yield strengths were over 1100 MPa within the CGHAZ and FGHAZ, and that these values were approximately double the yield strength of the base material (~500 MPa).…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…The strengths of the fusion zone and each sub-zone within the HAZ were increased mainly by the generation of martensite. Some researchers [39,40] have investigated the correlation between the microstructure and the fracture toughness within the heat affected zone in SA508 steel. Lee et al [40] reported that the yield strengths were over 1100 MPa within the CGHAZ and FGHAZ, and that these values were approximately double the yield strength of the base material (~500 MPa).…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…In addition to the location of carbon, the substitutional elements (Mn, Cr, Mo, Si …. etc) are soluble in the BCT martensite structure and they strongly disturb the local environment around iron atoms [12,13]. Thus, the observed three magnetic sub-spectra [MFe1, MFe2 and MFe3] may depend on the location of the carbon atoms and/ or the substitutional elements at the first or the second nearest interstitial sites, and may be further.…”
Section: Resultsmentioning
confidence: 99%
“…The intercritically reheated coarse-grained (ICRCG) HAZ near the weld fusion line, which is generally known as the most brittle region in HAZs, was considered the local brittle zone. [13,27] According to the thermal flow formula of Rosenthal, [27,28] the peak temperature (T p ) and cooling time between 800 °C and 500 °C (᭝t 8/5 ) were set to be 1350 °C and 23 seconds, respectively, for the local brittle zone. Thermal-cycle simulation conditions are shown in Table II.…”
Section: Methodsmentioning
confidence: 99%